Traces of cultural and personal values on sustainable consumption: An analysis of a small local swap event in Izmir, Turkey - Uckan Yuksel, Can; Kaya, Cigdem (Wiley, 2020)
AbstractA shift to the use of more eco‐friendly products and production methods is not sufficient to reverse the negative impacts of the Anthropocene period. Irrational overconsumption and production patterns should be abolished and redesigned to remain within the Earth's carrying capacity. Over‐consumption in Turkey is a part of the problem. At the juncture of Europe and Asia, Turkey has a wide variety of consumer behaviors, ranging from conservative habits to shopping sprees, especially with the rapid transition to an open economy in developing cities with contemporized lifestyles. On the one hand, consumption and material culture have quickly diffused among the younger population, who have an important share in the demographic structure and who adopt new information technologies and follow global trends. On the other hand, sharing and collaboration are core elements of the established culture. With that notion in mind, Karsiyaka municipality and the alternative education cooperation BBOM Izmir organized a swap event. The aim of the research, was to discover the views of participants on sustainability and swapping as an alternative collaborative consumption method. The results of the interviews and observations from the swap event revealed the traces of personal and cultural values on the participants' perspectives on sustainability concept and swapping. The results also showed correlations and differences with the literature. The perceptions and expectations of local consumers about swap and the concept of sustainability are mismatched with what we profoundly need for our goal of sustainability.